Identification of prototypes from Ligustri Lucidi Fructus in rat plasma based on a data‐dependent acquisition and multicomponent pharmacokinetic study. (20th April 2020) - Wang, Yucheng; Feng, Keyu; Li, Mengrong; Han, Lifeng; Wang, Weiqiang; Si, Dandan; Chen, Xiaopeng; Yang, Wenzhi; Gao, Xiumei; Liu, Erwei
Abstract: The identification and quantization of traditional Chinese medicine (TCM) are a challenge for researchers and industry. Using untargeted analytical methods, the in vivo detection and identification of TCM compounds are difficult because of the significant interference of endogenous substances. Fortunately, the ongoing development of new analytical technologies, especially Q‐Orbitrap–MS, offers some solutions. Our team developed a holistic MS method, combining untargeted data‐dependent MS 2 (dd‐MS 2 ) modes to extensively identify TCM prototypes in vivo. The method was successfully applied to the analysis of Ligustri Lucidi Fructus (LLF). LLF is a widely used TCM with a remarkable nourishing effect on the liver and kidney. In the study, we aimed to identify the prototypes in rat plasma after oral administration of LLF extract. Following separation on an HSS T3 column, LLF extract and rat plasma were performed in untargeted dd‐MS 2 mode. Forty‐seven compounds were characterized in rats plasma as prototypes of LLF extract. Furthermore, seven major prototypes were chosen as pharmacokinetic markers to investigate LLF's pharmacokinetic properties. The results provides comprehensive determination of compounds in LLF both in vitro and in vivo, which is important for quality control, pharmacology studies and clinical use of LLF.